Evaluating the Efficacy of VitalStim Electrical Stimulation Combined with Swallowing Function Training for Treating Dysphagia following an Acute Stroke - Liang, Yu (2021)
OBJECTIVES: This study explored the clinical efficacy of VitalStim electrical stimulation combined with swallowing function training for patients with dysphagia following an acute stroke. METHODS: Seventy-two patients with dysphagia following an acute stroke were admitted to our hospital and were further divided into two groups using prospective research methods. There were 36 cases in each group according to the random number table method. The control group received conventional medical treatment and swallowing function training while the experimental group received conventional medical treatment and VitalStim electrical stimulation combined with swallowing function training. RESULTS: The overall response rate of the experimental group (94.44%) was higher than that of the control group (77.78%), and the difference was statistically significant (p<0.05). Compared with before treatment, the upward and forward movement speeds of the hyoid bone, anterior movement speed, the grading score of the Kubota drinking water test, Caiteng's grading score, serum superoxide dismutase, 5-hydroxytryptamine, and norepinephrine levels, Fugl-Meyer Assessment score, and multiple quality of life scores of the two groups showed improvement after treatment. While the standard swallowing assessment score, serum malondialdehyde level, and National Institutes of Health Stroke Scale score decreased, the aforementioned indices showed a significant improvement in the experimental group (p<0.05). CONCLUSION: The results of this study indicate that VitalStim electrical stimulation combined with swallowing function is effective for treating dysphagia following an acute stroke. It can effectively improve swallowing, neurological, and limb motor functions, reduce complications, promote physical recovery, and improve overall quality of life of patients.